Aircraft noise as a problem of environment protection - Токарев, В. І.; Запорожець, О. І. (Proceedings of National Aviation University (archive), 1998)
One of the factors of negative aviation impact on an environment is the noise, which is under consideration of the requirements of the international standards - declared at ICAO Annex 16 (vol. 1) to the Convention on international civil aviation. The aspects of influence of the aircraft noise on natural environment existing outside of an aircraft and environment, which is formed inside the aircraft cabins, are considered. The analysis of formation and assessment of aircraft noise impact is carried out. The measures of their reduction are investigated